Pengaruh Pendidikan Dan Pelatihan, Kerjasama Tim Dan Komitmen Organisasi Terhadap Kinerja Pengurus Koperasi Primer Provinsi Kepulauan Riau Melalui Motivasi Sebagai Variabel Intervening - Mukhry, Basrawi; Satriawan, Bambang; Sajiyo (Program Studi Manajemen FEBM UMRAH, 2025)
The Riau Islands (Kepri) Provincial Government is actively developing cooperatives to improve the competitiveness and professionalism of cooperatives in the region. In fact, by 2024, with 176 cooperatives and 138 active cooperatives, only 26 had submitted their RATs. This study used a quantitative method with a descriptive quantitative approach. Based on the results of the data analysis, it can be concluded that education and training significantly influence performance by improving employee abilities, skills, and motivation. Teamwork also significantly influences performance, although it does not directly influence motivation. Organizational commitment has been shown to improve performance through employee responsibility and loyalty, as well as increasing work motivation. Motivation itself is an important factor driving better performance. Education and training play a role in increasing motivation, which then contributes to improved performance indirectly as a mediator. Conversely, teamwork has no significant effect on motivation or performance through motivation. Organizational commitment also has a positive impact on performance, both directly and indirectly through